Variants in the DYX2 locus are associated with altered brain activation in reading-related brain regions in subjects with reading disability - Cope, Natalie (2012)
Reading disability (RD) is a complex genetic disorder with unknown etiology. Genes on chromosome 6p22, including DCDC2, KIAA0319, and TTRAP, have been identified as RD associated genes. Imaging studies have shown both functional and structural differences between brains of individuals with and without RD. There are limited association studies performed between RD genes, specifically genes on 6p22, and regional brain activation during reading tasks. Using fourteen variants in DCDC2, KIAA0319, and TTRAP and exhaustive reading measures, we first tested for association with reading performance in 82 parent-offspring families (326 individuals). Next, we determined the association of these variants with activation of sixteen brain regions of interest during four functional magnetic resonance imaging-reading tasks. We nominally replicated associations between reading performance and variants of DCDC2 and KIAA0319. Furthermore, we observed a number of associations with brain activation patterns during imaging-reading tasks with all three genes. The strongest association occurred between activation of the left anterior inferior parietal lobe and complex tandem repeat BV677278 in DCDC2 (uncorrected p=0.00003, q=0.0442). Our results show that activation patterns across regions of interest in the brain are influenced by variants in the DYX2 locus. The combination of genetic and functional imaging data show a link between genes and brain functioning during reading tasks in subjects with RD. This study highlights the many advantages of imaging data as an endophenotype for discerning genetic risk factors for RD and other communication disorders and underscores the importance of integrating neurocognitive, imaging, and genetic data in future investigations.